Truceless war : Carthage's fight for survival, 241 to 237 BC - Hoyos, B. D. (B. Dexter), 1944- (History of warfare ;, 2007)
A major rebellion against Carthage of mercenary troops and oppressed North African subjects almost ended her existence, a story vividly recorded by the historian Polybius. This title reconstructs what happened and why.